Kebijakan Pemerintah dalam Penanaman Modal Asing Di Kota Batam 2017-2019 - Edison Edison; Dhani Akbar (Jayapangus Press, 2021)
Tourism is often seen as an economic engine of foreign exchange exchange for economic development for a country, including Indonesia. However, in principle tourism has a broader spectrum of development for a country. Most of the tourists in Batam tourism especially come from Singapore and Malaysia to enjoy tourism by shopping. For this reason, it is the government's seriousness to develop the tourism industry, as a supporter of the community's economy. The condition of Batam City is comfortable and safe in investing in Batam City, investors are interested in investing in the business they are interested in. In order to make it easier for investors to obtain licenses and non-licensed investments in carrying out business activities to produce goods or services through ownership of domestic and foreign capital. The government has issued rules and regulations regarding services in sector investment. The tourism sector has the potential to create employment and business opportunities and to increase and equalize the incomes of people and the region.